Transformational Leadership, Organizational Citizenship Behaviour, and Performance Among Lecturers and Administrative Staff: A Multigroup Analysis - Odha Meditamar, Muhd.; Rasmita; Sujadi, Eko (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
development of educational institutions. Several factors are predicted to affect performance, including transformational leadership and organizational citizenship behaviour (OCB). This study investigates the direct effect of transformational leadership and OCB on performance. In addition, we also tested the mediating effect of OCB between transformational leadership and performance relationships. The population in this study were all lecturers and administrative staff of Institut Agama Islam Negeri Kerinci, with the status of civil servants totalling 254 people. Based on this number, 152 people who would be the research sample were obtained. Researchers adapted three research scales for data collection: Individual Work Performance (IWP-1.0), the Organizational Citizenship Behaviour Scale, and The Global Transformational Leadership scale (GTL). Hypothesis testing using Structural Equation Modeling - Partial Least Square (SEM PLS) through the SmartPLS. The research findings showed a significant effect of transformational leadership and OCB on performance; OCB also has a mediating effect on these relationships. Testing using multigroup analysis proved that there was a significant effect on all genders, but greater significance was found for male respondents. Higher education leaders can begin to consider performance metrics that include OCB as an integral part of faculty and administrative staff performance appraisals. This policy will encourage them to perform with sincerity beyond fulfilling routine tasks. In addition, university leaders also need to display transformative leadership to support the achievement of better performance of lecturers and administrative staff.